Development Impact of Social Media - Ackland, Robert (World Bank, Washington, DC, 2016)
This paper assesses the role of social media in social and economic development. The web and in particular, social media such as social network sites (e.g. Facebook) and microblogs (e.g. Twitter), allows ordinary citizens to connect with one another and share information via computer-mediated networks. This behavior is often explicitly or implicitly networked (for example, people ‘friend’ one another on Facebook and ‘follow’ one another on Twitter, leading to the formation of social and information-sharing networks). For that reason, the paper uses an analytical framework that draws from the extensive literature on social networks. It summarizes research on social networks, social learning and development and use this as a basis for assessing the potential impact of social media on social and economic development.